Pengaruh Lama Penyimpanan dan Bentuk Substitusi Ubi Ungu terhadap Jumlah Total Mikroorganisme pada Bolu Kukus - Renowening, Yuniars, Dwi Sarbini, S.ST., M.Kes, Eni Purwani, S.Si., M.Si (2016)
Steamed sponge is a food that preferred by Indonesian people. The main ingredients of a sponge cake is flour. Efforts should be made to reduce the use of wheat flour was by developing local food ingredients. Purple sweet potato has the advantage that capable be substituents for other materials either in the form flour or puree. Storage duration and form of substituents will affect the total number microorganisms of steamed sponge.This research aims To find out the influence of storage duration and form of substitution of purple sweet potato towards total number microorganisms of steamed sponge. This research uses completely randomized design. Substitution of potato flour purple and purple potato puree which used are 40%. Furthermore variations of storage duration were 0 hours, 24 hours and 48 hours. Data were analyzed using Kruskal Wallis and T-Test Independent The result of research shows the influence of storage duration steamed sponge with a kind of substitution of purple sweet potato flour has the highest total number of microorganisms on the storage of 48 hours (2,83x106cfu / ml) and steamed sponge purple sweet potato puree substitution also had the highest total number of microorganisms on the storage of 48 hours (8, 31x105cfu / ml). The test results TPC (Total Plate Count) indicates that there was no influence of storage duration and form of substitution of purple sweet potato towards total number microorganisms of steamed sponge. Keywords : purple sweet potato flour, purple sweet potato puree, the total number of microorganisms, during storage.